Low-dose methotrexate in dermatology: the utility of serological monitoring in a real-world cohort. (19th May 2022) - Hajar, Tamar; Latour, Emile J.; Haynes, Dylan; Topham, Christina; Hill, Emma E.; Simpson, Eric L.; Greiling, Teri M.
Abstract: When prescribing low-dose methotrexate, frequent serological testing is recommended in the dermatologic literature, although much of the supporting data is extrapolated from non-dermatologic conditions. We performed a retrospective cohort study to determine the cumulative incidence and timing of low-dose methotrexate-associated serological abnormalities over the first year of therapy, in a pragmatic cohort of patients with dermatologic compared to non-dermatologic diagnoses. Laboratory values recorded included white blood cell count, hemoglobin, platelet count, estimated glomerular filtration rate, alanine aminotransferase, and aspartate aminotransferase. Among 1376 patients, there were no cases of methotrexate-associated grade 4/very severe lab abnormality or fatality. Baseline risk factors associated with moderate-to-severe lab abnormalities included non-dermatologic diagnoses, low hemoglobin, low estimated glomerular filtration rate, and elevated transaminases. The incidence of moderate-to-severe lab abnormalities was 4.4% among all patients, 3.1% among patients with dermatologic diagnoses, and 2.3% among patients with normal baseline lab values. Lab abnormalities led to discontinuation of therapy in 0.8% of patients. Serious changes did not occur in the first two weeks of therapy. We conclude that the cumulative incidence of low-dose methotrexate-associated lab abnormality was lower in patients with dermatologic diagnoses or normal baseline testing and these factors may be used to adjust monitoring practices.